EFL Pre-Service Teacher Constructs and Practices of Critical Thinking - Putu Suarcaya (Journal of English Education and Teaching, 2023)
Most studies on critical thinking involving preservice teachers (PST) focused on their perception about critical thinking and learning activities, how to improve critical thinking skills through various learning methods, techniques, and strategies in the classroom, and classroom teacher-learner interaction to facilitate critical thinking activities. Irrespective of the existing studies conducted on critical thinking in the classroom, it is still an important issue for PSTs in especially investigating how the construct of critical thinking defined by the PSTs is translated into learning objectives as the learning objectives become the foundation in designing learning activities. This study was, therefore, conducted to explore both the preservice teachers’ construct of critical thinking and how the construct is translated into learning objectives in their lesson plans. This current study adopted a case study model emphasizing on the occurrence of cases in the field for the sake of seeking answers to those cases. The respondents of this study were six PSTs conducting their practice teaching at vocational and senior high school for three months. Data collected consist of two types, namely: data from written interview about construct of PSTs’ critical thinking and data dealing with critical thinking practices in a form of design of learning activities collected from lesson plans. Findings show that the respondents are able to define what critical thinking is based on the keywords signifying what critical thinking is. However, crosscheck on how the construct is transferred into the learning objectives set in the lesson plan does not show encouraging results.